7(x-8)=7(x+3)

Simple and best practice solution for 7(x-8)=7(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-8)=7(x+3) equation:


Simplifying
7(x + -8) = 7(x + 3)

Reorder the terms:
7(-8 + x) = 7(x + 3)
(-8 * 7 + x * 7) = 7(x + 3)
(-56 + 7x) = 7(x + 3)

Reorder the terms:
-56 + 7x = 7(3 + x)
-56 + 7x = (3 * 7 + x * 7)
-56 + 7x = (21 + 7x)

Add '-7x' to each side of the equation.
-56 + 7x + -7x = 21 + 7x + -7x

Combine like terms: 7x + -7x = 0
-56 + 0 = 21 + 7x + -7x
-56 = 21 + 7x + -7x

Combine like terms: 7x + -7x = 0
-56 = 21 + 0
-56 = 21

Solving
-56 = 21

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x+4=4x-4 | | U/2-3=6 | | q^2+160q-8000=0 | | 2x+4x+4=12 | | 17x+14y=21z | | u+-4=9 | | 2(x+3)=9x+2-7x+4 | | z+(-29)=-96 | | -10f=9-9f | | x+(x+.3)=200000000 | | 3x^2+2x=-5x+20 | | 4x(3x^2-2x+6)= | | 17x*14x=1247 | | 5-1/3x=14 | | -4b=-5b-6 | | 7x^2=9-4x | | 6=r+2 | | 49y^2-25x^2= | | -3(12+-2.3y)+3y=-6 | | .5x^2-1x-.5=0 | | 4(13-1.5y)= | | 3t^2+16t+5= | | 3c=5-2c | | 12+r=47 | | 9(2x-1)-17x=9 | | -15.3=-7.5k | | 36=1.8x | | 96=.25x | | 2.50+3.75=3.35(50) | | 2.50+3.75=3.35*50 | | 5-3(w+9)=w-7 | | 4(x+1)=4(x-2) |

Equations solver categories